Development of Innovative Chemical Methods for Analyzing Heavy Metals and their Impact on Liver and Kidney Function Markers - Hussein, Yusur Saadi; Naji, Abbas Ali Abbas; Hawar, Abbas Sami Jawhar; Wasmi, Amal Majid Ibrahim (American Journal of Biomedicine and Pharmacy, 2025)
Heavy Metals are widely dispersed through the environment due to urbanization, industrialization, energy generation, and agricultural activities. Seven metals are traditionally regarded as heavy metals (As, Cd, Cr, Co, Pb, Hg and Ni), and their contamination varies across geographical regions. Many are ranked by the US Agency for Toxic Substances and Disease Registry as priority pollutants because of the health threats they pose. Chronic exposure to heavy metals through contaminated food or water can cause, depending on exposure level and exposure route, acute or chronic damage to various human organs and tissues, including the liver, kidneys, brain, and skin. The liver is one of the primary organs to be damaged by heavy metals. To monitor heavy metal exposure in polluted environments, several conventional analytical methods have been established, including atomic absorption spectroscopy (AAS), inductively coupled plasma-atomic emission spectrometry (ICP-AES), and inductively coupled plasma-mass spectroscopy (ICP-MS). These methods are limited for biological samples, being laborious, expensive, and time-consuming. Due to the highly selective nature of Hg(II), a highly sensitive colorimetric method based on the colour change of gold nanoparticles (AuNPs) was developed. The AuNPs’ surface was functionalized with PEG 20000 to prevent salt-induced aggregation in the presence of HEPES buffer and the mechanism is based on Tyndall effect. Using this system, Hg2+ can be specifically detected at the micrograms per litre level by the naked eye, and the limit of detection (LOD) was calculated to be as low as 23 μg L−1, which is significantly below the strict upper limit in drinking water (50 μg L−1), set by the world health organization (WHO). More significantly, this assay can be easily extended to the on-site semi-quantitative detection of Hg2+ by a biomimetic AuNPs-coated paper device developed for rapid screening assays.